Pengaruh Literasi Keuangan terhadap Keputusan Investasi pada Generasi Muda - Nur, Sulistiwati; Anwar, Anwar; Aslam, Annisa Paramaswary (IAIN Parepare, 2025)
This study examines the effect of financial literacy on investment decision-making among young individuals in Benjala Village, Bontobahari District, Bulukumba Regency, Indonesia. Financial literacy is conceptualized across four dimensions: fundamental financial knowledge, income and expenditure management, risk comprehension, and the adoption of financial technology. Investment decisions are assessed based on participants’ understanding of financial products, readiness to face risk, and the alignment of investment actions with personal financial goals. Employing a quantitative research design, the study surveyed 360 purposively selected respondents using a structured questionnaire. Data were analyzed using descriptive statistics and simple linear regression. The findings indicate that financial literacy has a statistically significant and positive impact on investment decision-making. While respondents demonstrated adequate understanding of basic financial management and risk, notable gaps were observed in the use of financial technology and long-term investment planning. These results highlight the importance of strengthening financial literacy, particularly in its practical applications, to support more informed, rational, and goal-oriented investment behavior among youth. The study underscores the need for targeted financial education initiatives and suggests avenues for future research in broader and more diverse population settings.